The Crisis of Religious Identity in the Young Generation - Bako, Anggreni; Ananda, Azwar (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This research aims to determine the impact of identity crisis on adolescents due to online games in Simberuna Village, Sitellu Tali Urang Jehe District, Pakpak Bharat Regency. This research is a qualitative descriptive type of research that describes and explains in the form of an in-depth description and analysis of a real situation and situation, namely regarding "Identity Crisis in Adolescents Due to Online Games in Simberuna Village, Sitellu District, Tali Urang Jehe, Pakpak Bharat Regency". This type of descriptive research is more concerned with explaining the relationship between the symptoms and targets studied. The results obtained from this study are (1) Adolescents experience an identity crisis because they have problems with their ability to control emotions, have problems placing themselves with their peers, have problems with their appearance, and do not get the right figure to achieve a good self-identity because it is fun to play games online. (2) The impact caused by online games is being unable to make important decisions about themselves, reduced interest in learning from teenagers who are already addicted, often procrastinating work, and not socializing with the surrounding environment because they are engrossed in playing online games.